Seasonal dynamics of bird communities in urban forests of a Mediterranean city (Montpellier, Southern France) - Caula, Sabina (2014)
We evaluated the richness, composition and abundance of bird communities in three urban forests of Mediterranean France during winter and spring. The urban forests differed in size, composition, structure, age of vegetation, and location relative to the city centre. Estimated species richness across all three urban forest parks was 45 species. Twenty six (26) species were recorded in both winter and spring, whereas ten species were recorded only in spring, and six were recorded only in winter. Distribution, turnover, and type of bird foraging guild were related to characteristics of each urban forest and season. During spring migration, more species were recorded in sampling units (250 × 250 m) within the largest and most natural urban forest located in the outskirts of Montpellier, whereas during winter, more species were recorded in the most urbanized park (i.e., a botanical garden dominated by exotic vegetation), which was located in the city centre. Insectivorous birds were more abundant in winter, whereas seedeaters associated with wooded habitats were recorded more frequently in spring. Our results suggested that different kinds of urban forests are important modulators of urban bird communities and they are necessary to maintain the diversity of migratory and resident birds as well as increasing the environmental quality of urban areas.